Integrating Waqf into the Halal Meat Supply Chain: Strengthening Indonesia’s Halal Economy - Panglima Thariq Al Huda; Yuliadi, Imamudin; Dewanti, Diah Setyawati (Islamic Economics and finance in Focus, 2026)
Indonesia, with the largest Muslim population globally, holds significant potential for a sustainable halal economy. Strengthening halal industry infrastructure, particularly in the halal meat supply chain, requires innovative financing mechanisms. This study develops a conceptual framework for integrating productive waqf as a strategic financing instrument to support halal-certified infrastructure, enhance supply chain coordination, and promote inclusive economic growth. Using a qualitative descriptive approach based on an interpretive literature review, the study synthesizes academic, institutional, and policy sources related to waqf governance, Islamic social finance, and halal value chain development. Findings indicate that productive waqf can function as institutional capital to address infrastructure gaps, empower communities, and reinforce halal-compliant enterprises. The study contributes to the literature on Islamic social finance by conceptualizing waqf as infrastructure financing within halal supply chains and provides policy insights for policymakers, regulators, and Islamic financial institutions to strengthen a sustainable halal ecosystem in Indonesia.